PELATIHAN PEMBUATAN PUPUK KOMPOS DAN POC DI KELURAHAN TEMINDUNG PERMAI RT. 09 KOTA SAMARINDA - Deny Kurniawan; Harun Saputra; Aura Natasya Nuzlia Haqqi; Elsa Miranti; Muhammad Sultan Firdaus (JURNAL DAYA-MAS, 2025)
This community service program aimed to provide education and hands-on training to the residents of Temindung Permai Subdistrict, RT. 09, Samarinda City, on how to utilize organic waste through the stacked bucket composting method. The program was a collaboration between lecturers and students of the Environmental Health Diploma Program at Universitas Muhammadiyah Kalimantan Timur. The activities began with a socialization session, followed by a direct composting practice involving the local RT leader and members of the Dasawisma women’s group. Organic waste was fermented using EM4 and molasses, then left to decompose for three weeks. During the composting process, temperature, humidity, and pH measurements were taken as indicators of decomposition success. The results showed an increase in the pH of the liquid compost from 3 to 4, and the solid compost from 5.4 to 5.9, with a stable temperature range between 26.7–27.5°C, indicating optimal microbial activity. This program successfully improved the community's understanding and skills in independently managing household organic waste, offering a practical and environmentally friendly solution to domestic waste problems.